2005
DOI: 10.1381/096089205774859281
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surgically-Induced Weight Loss on the Knee Joint

Abstract: Surgically-induced weight loss is an effective, rapid and dependable means of reversing the radiological signs of early changes associated with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 12 publications
2
49
0
2
Order By: Relevance
“…It is important to notice that even individuals without OA diagnosis presented with high WOMAC scores, which points out the functional limitation imposed by the presence of obesity. Several studies have shown an improvement of symptoms and quality of life in obese osteoarthritic subjects treated with bariatric surgery 1,7,8 . The main limitation of this study is that the sample is composed of individuals referred for surgical treatment of obesity in the public system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to notice that even individuals without OA diagnosis presented with high WOMAC scores, which points out the functional limitation imposed by the presence of obesity. Several studies have shown an improvement of symptoms and quality of life in obese osteoarthritic subjects treated with bariatric surgery 1,7,8 . The main limitation of this study is that the sample is composed of individuals referred for surgical treatment of obesity in the public system.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the obvious mechanical overload, cytokines associated with adipose tissue, including adiponectin, leptin and resistin also influence the onset and worsening of OA through direct degradation of the joint or inflammatory processes stimulation 17 . Literature shows clear relationship between weight loss through bariatric surgery and OA symptoms improvement 1,7,8 . Prevalence of osteoarthritis in Brazilian adult population is 4.14% according to the only existing study on the subject 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there may be a role for bariatric surgery in preventative healthcare. An interesting study by Abu-Abeid et al [27] studied 64 patients with knee pain and early signs of OA on radiographs, who underwent bariatric surgery. At 3-month follow-up, the joint space increased an average of 0.65 mm with an associated average BMI reduction of 6.3 kg/m 2 which correlated with improved pain-control.…”
Section: Bariatric Surgery Link To Improved Osteoarthritismentioning
confidence: 99%
“…Any operative intervention offered can provide excellent results in terms of weight loss and improvements in associated comorbidities, including osteoarthritis. 1,3 Such procedures will not only reduce the risks of subsequent orthopaedic surgery for these patients but, in some cases, postpone or exclude the need for such treatment. 4 Excellent results have already been reported for arthroplasty following bariatric surgery.…”
Section: O M M E N T O Nmentioning
confidence: 99%